The association between pulmonary tuberculosis recurrence and exposure to fine particulate matter and residential greenness: A population-based retrospective study - Yuanzhi Di; Ying Peng; Xiaogang Hao; Henan Xin; Tonglei Guo; Jiang Du; Xuefang Cao; Lingyu Shen; Juanjuan Huang; Yijun He; Boxuan Feng; Zihan Li; et al. (One Health)
Background and objective: To assess the association of pulmonary tuberculosis (PTB) recurrence with fine particulate matter (PM2.5) and residential greenness using a population-based retrospective study design. Methods: All incident PTB patients, registered in Tuberculosis Information Management System (TBIMS) from 2015 to 2019 in Quzhou City, China, were included. The data on PM2.5 exposure was extracted from the China High Air Pollutants dataset and the level of greenness was estimated using the Normalized Difference Vegetation Index (NDVI) values around the patient's residence. The Cox proportional hazards models were used to quantify the risk of PTB recurrence. Results: 6732 Eligible PTB incident patients were included in the study with a mean age of 56.86 years and a median follow-up time of 750 days. Recurrence was observed in 554 patients (8.2 %). Exposure to NDVI was observed to be negatively associated with PTB recurrence (HR: 0.86, 95 % CI: 0.75–0.98 per 0.1-unit increase). The strength of the association between higher PM2.5 and the risk of PTB recurrence was greater than that of lower PM2.5 concentrations in both low and high NDVI groups (HR:6.62 and 4.35, p-interaction <0.001). Conclusions: Our findings suggest that higher PM2.5 exposure might increase the risk of PTB recurrence, while residential greenness might have a protective effect. Like other chronic respiratory diseases, prevention and control of PTB will also benefit from comprehensive environmental management.